Allosteric regulation of deubiquitylase activity through ubiquitination - Faggiano, Serena; Menon, Rajesh P.; Kelly, Geoff P.; Todi, Sokol V.; Scaglione, K. Matthew; Konarev, Petr V.; Svergun, Dmitri I.; Paulson, Henry L.; Pastore, Annalisa (Frontiers in Molecular Biosciences, 2015)
Ataxin-3, the protein responsible for spinocerebellar ataxia type-3, is a cysteine protease that specifically cleaves poly-ubiquitin chains and participates in the ubiquitin proteasome pathway. The enzymatic activity resides in the N-terminal Josephin domain. An unusual feature of ataxin-3 is its low enzymatic activity especially for mono-ubiquitinated substrates and short ubiquitin chains. However, specific ubiquitination at lysine 117 in the Josephin domain activates ataxin-3 through an unknown mechanism. Here, we investigate the effects of K117 ubiquitination on the structure and enzymatic activity of the protein. We show that covalently linked ubiquitin rests on the Josephin domain, forming a compact globular moiety and occupying a ubiquitin binding site previously thought to be essential for substrate recognition. In doing so, ubiquitination enhances enzymatic activity by locking the enzyme in an activated state. Our results indicate that ubiquitin functions both as a substrate and as an allosteric regulatory factor. We provide a novel example in which a conformational switch controls the activity of an enzyme that mediates deubiquitination.